(3GdYdGbGJ GdYGeI h GdJfejI (B/s - (3GdRhHYj, YQSGf jhSas ((3YeGf(B;(3GdCQOf (B:s (3OGQ CSGeI ddfTQ h GdJhRjY (B;(3fHdGA fGTQhf h ehRYhf ,s, 2016)
(3bSe gPG GdaUd Gdi (B5(3aUhd JfGhd GdaUd GdGhd GdYdGbGJ GdYgGeI h JWhQgG h cGf HKdGK eHGMK GdGhd eaghe GdYdGbGJ GdYGeI h GdKGfj GdYdGbGJ GdYGeI h YdGbJgG HH GdYdhe h GdGfTWI h GdKGdK JWhQ GdYdGbGJ GdYGeI GeG GdaUd GdKGfj acGf HKdGK eHGMK JfGhd GdGhd GgejI GdYdGbGJ GdYGeI h GdKGfj GgOGa GdYdGbGJ GdYGeI h GdKGdK hXGFa GdYdGbGJ GdYGeI h LGA GdaUd GdKGdK HYfhGf GdYGedhf aj GdYdGbGJ GdYGeI h LeGgjQgG h cGf HeHMKHf GdGhd JfGhd GdYGedhf aj GdYdGbGJ GdYGeI h GdKGGfj LeghQ GdYdGbGJ GdYGeI GeG GdaUd GdQGHY GNdGbjGJ GdYdGbGJ GdYGeI h GJUGdGJgG aLGA HKdGKI eHGMK JfGhd GdGhd GNdGbjGJ GdYdGbGJ GdYGeI h GdKGfj GdGJUGd aj GdYdGbGJ GdYGeI h GdKGdK GSGdjH hhSGFd GdGJUGd aj GdYdGbGJ GdYGeI GeG GdaUd GdNGeS acGf HYfhGf GdYdGbGJ GdYGeI h GdJfejI hcGf HKdGKI eHGMK JfGhd GdeHMK GdGhd eaghe GdJfejI h GdKGfj GdYdGbGJ GdYGeI h GdJfejI h GdKGdKQ GdGJUGd h OhQg aj GdJfejIs
(3HjHd(B.:141-152s
Keywords: (3GdEOGQIs; (3hSGFd GdEJUGds; (3GdEJUGds; (3GdYdGbGJ GdYGeIs